Кон Lars-Erik Caderman (Ed.), Constructing Europe’s Identity: The External Dimension: Për Lars-Erik Caderman (Ed.), Constructing Europe’s Identity: The External Dimension - Badarevski, Bobi; Ahmeti, Lindita (Identities: Journal for Politics, Gender and Culture, 2005)
Author(s): Bobi Badarevski | Боби Бадаревски Title (Macedonian): Кон Lars-Erik Caderman (Ed.), Constructing Europe’s Identity: The External Dimension Title (Albanian): Për Lars-Erik Caderman (Ed.), Constructing Europe’s Identity: The External Dimension Translated by (Macedonian to Albanian): Lindita Ahmeti Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 4, No. 1-2 (Summer - Winter 2005) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 349-350 Page Count: 2 Citation (Macedonian): Боби Бадаревски, „Кон Lars-Erik Caderman (Ed.), Constructing Europe’s Identity: The External Dimension“, Идентитети: списание за политика, род и култура, т. 4, бр. 1-2 (лето - зима 2005): 349-350. Citation (Albanian): Bobi Badarevski, „Për Lars-Erik Caderman (Ed.), Constructing Europe’s Identity: The External Dimension“, përkthim nga Maqedonishtja Lindita Ahmeti, Identities: Journal for Politics, Gender and Culture, Vol. 4, No. 1-2 (Summer - Winter 2005): 349-350.